DAMPAK PANDEMI COVID-19 TERHADAP RETURN SAHAM SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020 - Annisa Mazid; Erna Listyaningsih; Wiewiek Indriani (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This research aims to find out how the impact of Covid-19 on the return of property and real estate sector shares is projected through differences in Return and Abnormal Return before and after the announcement of the first Covid-19 case in Indonesia. In this study used a type of secondary data obtained from the official website of the Indonesia Stock Exchange. The population in this study is all property and real estate sector companies listed on the Indonesia Stock Exchange. In sampling using purposive sampling techniques that use certain criteria. The data analysis technique in this study uses several methods, namely one sample t-test, paired sample t-test, and simple linear regression analysis. The results showed that the announcement of the first Covid-19 case in Indonesia had an effect on stock returns and abnormal return of shares shown through significant differences in abnormal returns before and after the announcement of the first Covid-19 case in Indonesia.